The State National Policy of Heritage Management: an assessment of the extinct RFFSA's non-operational properties management - Paiva, Claudio Cesar de [UNESP]; Fonseca, Sergio Azevedo [UNESP]; Fernandes de Paiva, Suzana Cristina [UNESP] (Escola Nacl Adm Publica-enap, 2017)
This paper's main objective is to report the research results which evaluated the Brazilian Federal Government real estate assets management policy. The focus of the research qualitative concerning the method, exploratory in its purpose, outlined as a single case study and using documental research and semi-structured screenplays for interviews as data collection instruments - was oriented to the management process of non-operating assets of the extinct RFFSA, seeking to evaluate, especially, the difficulties and challenges for the incorporation and allocation of approximately 52 thousand properties. The research revealed that, despite the new model of management adopted since the late 2000s, the Department of Heritage of the Federal Government (SPU) still presents the vicissitudes of an institution built under a patrimonial tradition, which does not guarantee compliance of the social function of public property.
Keywords: patrimonial administration; public goods; social function of property; federal administration